RELEVANSI NILAI-NILAI ETIKA ISLAMDALAM MENGHADAPI ISU BULLYING DAN KEKERASAN PADA ANAK USIA DINI - Elyaum Farihah (LPPM IAD Probolinggo, 2025)
Bullying and violence in early childhood is a worrying global phenomenon with long-term impacts on children's physical, psychological, social, and spiritual development. This study examines the relevance of Islamic ethical values as a comprehensive solution to address the issue of bullying and violence in early childhood. Using a qualitative approach with library research and content analysis methods, this study analyzes five fundamental values of Islamic ethics: akhlaq karimah (noble character), rahmah (universal compassion), adl (justice), hikmah (wisdom), and ukhuwah (universal brotherhood). Data were collected from primary sources (the Qur'an and Hadith) and secondary sources (scientific journals, books, research reports) relevant to the research topic. The results of the study indicate that Islamic ethical values have high relevance in the prevention and handling of bullying in early childhood. Akhlaq karimah serves as the foundation for character formation through the development of the qualities of ash-sabr (patience), at-tawadhu (humility), and ar-rifq (gentleness). The value of rahmah develops empathy and a protective attitude towards the weak. The concept of adl ensures fair treatment without discrimination, while hikmah provides wisdom in choosing appropriate intervention strategies. Ukhuwah creates an inclusive environment of brotherhood. Implementation can be done through three main approaches: (1) A family approach through parental role models and informal education at home; (2) An institutional approach with an integrated curriculum and a conducive school environment; (3) A community approach through community involvement and the use of technological media. Preventive strategies are carried out through early character formation and social sensitivity education, while curative strategies use a restorative approach and counseling based on Islamic values. Keywords: Islamic Ethics; Bullying; Child Violence; Early Childhood; Character Education.